Fighting the AIDS and HIV Epidemic : A Global Battle - Hinds, Maurene (USA Enslow Publishers, 2008)
Describes the history of the AIDS and HIV epidemic, the prevention and treatment of this disease, and its future impact on the world.
Include Color Illustrations and Index
Keywords: AIDS (Disease) -- HIV infections